Automatic Traffic Control Technologies for Remote Monitoring Of Unmanned Railway Gates - Anand, JV (Journal of Electronics and Informatics, 2020)
Continuous researches are done to improve technologies for developing effective, economical and productive solutions for preventing fatalities in the railway gates that are unmanned. Several solutions in this research field have been suggested but none of them are sufficiently effective to deploy them at the automated level crossings and fully eradicate human presence. Surveying the current methodologies and the pitfalls in them the paper has developed an efficient and cost effective remote monitoring for unmanned railway gates, enabling automated traffic control technologies and the wireless sensors. The paper scope in developing an automated traffic control in the unmanned railway gates in India.